Electrochemical Investigation of the Eu3+/2+ Redox Couple in Complexes with Variable Numbers of Glycinamide and Acetate Pendant Arms. Issue 43 (21st November 2017) - Burnett, Marianne E.; Adebesin, Bukola; Funk, Alexander M.; Kovacs, Zoltan; Sherry, A. Dean; Ekanger, Levi A.; Allen, Matthew J.; Green, Kayla N.; Ratnakar, S. James
Abstract : The Eu 3+/2+ redox couple provides a convenient design platform for responsive p O2 sensors for magnetic resonance imaging (MRI). Specifically, the Eu 2+ ion provides T 1w contrast enhancement under hypoxic conditions in tissues, whereas, under normoxia, the Eu 3+ ion can produce contrast from chemical exchange saturation transfer in MRI. The oxidative stability of the Eu 3+/2+ redox couple for a series of tetraaza macrocyclic complexes was investigated in this work using cyclic voltammetry. A series of Eu‐containing cyclen‐based macrocyclic complexes revealed positive shifts in the Eu 3+/2+ redox potentials with each replacement of a carboxylate coordinating arm of the ligand scaffold with glycinamide pendant arms. The data obtained reveal that the complex containing four glycinamide coordinating pendant arms has the highest oxidative stability of the series investigated. Abstract : The redox stability of Eu 3+ /Eu 2+ couple shifts to more positive values and closer to the aqua ion for complexes with softer donor atoms (amide oxygen) compared to harder donor atoms (carboxylate).